A Comprehensive Screening of the Interactors of Areca Palm Necrotic Ringspot Virus (ANRSV) HCPro2 Highlights the Proviral Roles of eIF4A and PGK in Viral Infection - Li Qin; Peilan Liu; Wentao Shen; Zhaoji Dai; Hongguang Cui (Plants)
The areca palm (Areca catechu L.), a medicinal tropical crop, hosts three novel viruses, areca palm necrotic ringspot virus (ANRSV), areca palm necrotic spindle-spot virus (ANSSV), and ANRSV2, which form a new genus Arepavirus in the family Potyviridae. Both viruses feature a unique tandem leader protease arrangement (HCPro1-HCPro2). To elucidate HCPro2’s role, this study identified its interaction partners in infected cells using affinity purification coupled with liquid chromatography-tandem mass spectrometry, a yeast two-hybrid system, and co-immunoprecipitation. Thirteen host proteins and five viral factors (HCPro1, 6K2, VPg, NIa-Pro, NIb) were validated as HCPro2 interactors. Among the host proteins interacting with HCPro2, the expression of five genes (NbeIF4A, NbSAMS1α, NbTEF1α, NbUEP1, and NbRan2) was upregulated under the condition of viral infection, while the expression of another five genes (NbpsbS1, NbPGK, NbchIP, NbClpC1A, and NbCysPrx) was downregulated. Functional assays showed that silencing NbeIF4A or NbPGK significantly reduced viral accumulation in Nicotiana benthamiana. These findings reveal HCPro2’s network of virus-host interaction, highlighting its critical role in viral pathogenesis. Further exploration of these interactions may clarify the evolutionary significance of tandem leader proteases and inform novel plant antiviral strategies.